Hate Speech: A Systematized Review - Paz, Maria Antonia; Montero Díaz, Julio; Moreno Delgado, Alicia (Sage Open, 2021)
This review focuses on papers on Hate Speech, particularly in legal and communication studies indexed in Web of Science. It analyzes output published in English and in Spanish as well as surveys the predominant disciplines in which these studies are written, their trend over time, by country, and type of document. This research is extended to determine the debates, lines of work of greatest interest, and the theories elaborated. The legal literature is intended to define hate speech and hate crime for the purposes of applying criminal sanctions. From the communication standpoint, the analysis of hate speech in the media is key to understanding the type of message used, its emitter, the way in which the message rallies supporters, and how they interpret the message. Spanish studies mostly fall within the legal area, in which they focus on cases of insult directed at the Catholic religion. We discuss the importance of interdisciplinarity and transversality and propose a mapping of hate speech that lends itself to comparisons between countries to assess measures to counteract their effects.
Keywords: hate speech; racism; xenophobia; gender; free speech; social media; JCR; Scopus